Wonderstruck : a novel in words and pictures - Selznick, Brian (New York : Scholastic, 2011)
Having lost his mother and his hearing in a short time, twelve-year-old Ben leaves his Minnesota home in 1977 to seek the father he never knew in New York City, and meets there Rose, who is also longing for something missing from her life. Ben's story is told in words; Rose's in pictures.
2
Keywords: American Museum of Natural History -- Juvenile fiction; Deafness -- Juvenile fiction; Deaf -- Juvenile fiction; Diorama -- Juvenile fiction; Families -- Juvenile fiction; Museums -- Juvenile fiction; Orphans -- Juvenile fiction; People with disabilities -- Juvenile fiction; Runaway children -- Juvenile fiction